Dinamika Luas Panen dan Produksi Padi di Kawasan Barsela Aceh: Bukti Empiris Data Panel 2018-2025 - Agus Wandra; Yasrizal Yasrizal; Hartini Hartini; Helmi Noviar; Rolis Juliansyah (Indo Publishing, 2026)
This study examines the effect of harvested area on rice production in the Barsela region of Aceh Province during 2018-2025. It highlights the importance of harvested area as a key agricultural production factor in explaining regional rice output across districts and cities. This study employs a quantitative approach using balanced panel data from eight districts and cities in the Barsela region, namely Aceh Jaya, Aceh Barat, Nagan Raya, Aceh Barat Daya, Aceh Selatan, Simeulue, Aceh Singkil, and Kota Subulussalam. The dataset covers the 2018-2025 period, resulting in 64 observations. Panel data regression is applied by comparing the Common Effect Model, Fixed Effect Model, and Random Effect Model. Model selection is conducted using the Chow test, Hausman test, and Lagrange Multiplier test. The Random Effect Model is selected as the preferred specification. The findings show that harvested area has a positive and statistically significant effect on rice production. The coefficient of harvested area is 5.204529 with a probability value of 0.0000, indicating that a one-hectare increase in harvested area is associated with an increase of approximately 5.20 tons of rice production. The Adjusted R-squared value of 0.772121 shows that harvested area explains 77.21 percent of the variation in rice production. This study provides district-level evidence on rice production in Barsela Aceh. The findings emphasize the importance of protecting productive paddy fields, controlling land conversion, improving irrigation, and strengthening agricultural infrastructure to sustain regional food security.